2013
DOI: 10.3991/ijoe.v9i6.2898
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Remote and Virtual Lab Engineering. Where are we in 2013?

Abstract: Abstract-This article is introducing latest developments and trends in remote and virtual technologies and their application in engineering education. The author gives an overview about the potential of utilizing remote engineering in engineering research, education and professional training, focusing on different kinds of technological characteristics. In conclusion, possible ways of further advancement are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…• Go-Lab -a new European Union portal housed at École Polytechnique Fédérale de Lausanne [11]. Each of these efforts foregrounds different sets of functionality, though recent papers and reviews [11,18] still indicate a focus on technical issues rather than pedagogical ones. Of these, Go-Lab appears to be taking a more comprehensive approach to meeting the needs of non-technical instructor end-users by enabling them to customize the online lab experience for their students [11].…”
Section: Online Lab Platformsmentioning
confidence: 99%
“…• Go-Lab -a new European Union portal housed at École Polytechnique Fédérale de Lausanne [11]. Each of these efforts foregrounds different sets of functionality, though recent papers and reviews [11,18] still indicate a focus on technical issues rather than pedagogical ones. Of these, Go-Lab appears to be taking a more comprehensive approach to meeting the needs of non-technical instructor end-users by enabling them to customize the online lab experience for their students [11].…”
Section: Online Lab Platformsmentioning
confidence: 99%
“…Even not all labs are available for public some of them can be accessed by asking the access from lab owner. Several labs described in the paper are developed on the frame of Life Long Learning program project, NetLab [8]. The concept is applied into practice for different target groups in Estonia, Germany and Finland.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive overview about current trends and situation is given in paper [8]. The paper is introducing latest developments and trends in remote and virtual technologies and their application in engineering education.…”
Section: State-of-artmentioning
confidence: 99%
“…A more detailed review on the integration and interoperability of remote laboratories can nowadays be found in [11] and [12]. A different approach for the integration of remote laboratories into a learning process is based on the extension of well-known learning contents standards, such as SCORM and IMS.…”
Section: State Of the Artmentioning
confidence: 99%